Emerging Biological Therapies in Severe Eosinophilic Asthma. Issue 2 (December 2016) - Hay, Bryan; Risaliti, Carleen; McCallister, Jennifer
Abstract A small fraction of patients with asthma have severe, persistent disease that is often refractory to standard therapy. To meet this need, a growing emphasis has been placed on the development of alternative, novel therapies and the ability to characterize those patients who are most likely to benefit from these therapies. The eosinophil has been identified as a primary mediator in airway inflammation and as a potential pharmacological target. This narrative review outlines the need for more phenotype-directed therapies in severe asthma, and discusses the supporting evidence for monoclonal antibodies directed against key pro-eosinophilic T-helper 2 (Th2) inflammatory cytokines as additive agents in the treatment of severe asthma with an eosinophilic phenotype.